Asas Praduga Tak Bersalah Sebagai Prinsip Konstitusional dalam Penegakan Hukum Pidana - Kholik, Muhamad Abdul; Zulfaidah, Rena (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The principle of presumption of innocence is a fundamental constitutional principle in the modern criminal justice system and is one of the main pillars in protecting human rights. This study analyzes the position and implementation of the principle of presumption of innocence as a constitutional principle in the enforcement of Indonesian criminal law with a special focus on Law Number 1 of 2023 concerning the Criminal Code (KUHP) and Law Number 20 of 2025 concerning the Integrated Criminal Justice System (SPPT), as a substitute for the Criminal Code. The research uses normative legal research methods with an analytical approach and comparison of the latest laws and regulations. The results of the study show that the 2023 Criminal Code and the new 2025 Criminal Code have provided more explicit and comprehensive recognition of the principle of presumption of innocence by integrating international human rights standards. However, its application in the field still faces significant challenges in the form of limited capacity of the apparatus, pressure of public opinion, and the gap between ideal norms and practical reality. The study concludes that continuous efforts are needed in increasing the capacity of law enforcement officials, socializing new regulations, and building a strong legal culture to optimally implement the principle of presumption of innocence in all stages of criminal law enforcement.